PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KANCING GEMERINCING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IX A SMP NEGERI 2 LIRIK - Nerisa marnola Nerisa marnola; Zuhri '; Sakur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research was classroom action research that aims to improve mathematics achievement with applied the cooperative learning technique of jingling studs. The subject of the research is students of class IX A SMP Negeri 2 Lirik in the first semester academic years 2014/2015, there are 23 students in the class who have heterogeneous academic ability. The research are two cycles, each a cycle has four stages, that are planning, implementation, observation, and reflection. Each end of the cycle of daily tests carried out. Data collected through observation and tests in the form of daily tests. Data analysis was performed with narrative descriptive analysis and descriptive statistical analysis. The qualitative analysis descriptive narrative showed that the teacher’s activities and students have done to the action of the first cycle to the second cycle. Most of students were active in learning process. Such as while they were doing the steps of learning, presenting students’ worksheet or questions, and giving the conclusion of learning. The descriptive statistical analysis showed the number of students who achieve a score of minimum mastery criteria increase in daily tests I and II. The number of students who achieve a score of minimum mastery criteria on basic, daily test I (first cycle) and daily test II (second cycle) are respectively 13.04%, 34.78%, and 69.57%. Results of this research indicates that the cooperative learning technique of jingling studs can improve students' mathematics achievement math class IX A SMP Negeri 2 Lirik. Key words: Mathematics learning outcome, Cooperative learning technique of jingling studs, Class action research